The Dynamics of the Question in the Quest for God - Navone, John (Journal of Dharma, 1987)
First, he must know who this God is who confronts him; then he must do something about it. Since God is tbat kind of God. Paul seems to be saying, therefore, I must find out and do whatever he commands me to do. To "know" the living God, in the biblical sense, is to live with him in doing his will. Our action must be in response to God's action. We must be with God in doing what he is willing and doing. God loves us; therefore, we must love one another (1 John 4: 19). It would be absurd to talk about knowing God if you did not also love your brother: Anyone who says, 'I love God', and hates his brother, is a liar, since a man who does not love the brother that he can see cannot love God, whom he has never seen. So this is the commandment that he has given us, that anyone who loves God must also love his brother (1 Jn 4 : 20-21).